Analysis Student’s Perception of Digital Social Media towards the Student’s English Writing Skill - Muslimah, Ima (Universitas Muhammadiyah Enrekang, 2023)
In education, social media play roles in language learning because they provide opportunities for English language learners to develop their writing skills. This research is qualitative by taking data from 14 students in English Education Department. The results of this study used a descriptive method. This study aims to find out the students’ perception of digital social media towards students’ English writing. The results of this study indicate that Students at Muhammadiyah University of Enrekang, English Education Study Program are familiar with and highly interested in social media and the internet. Students prefer utilizing social media for academic purposes over using books students. The majority of students believe that their use of social media improves their writing skills since they are conscious of their grammar (71,4%).